Effect of Long-Term Body-Mass-Based Resistance Exercise on Cognitive Function in Elderly People. (December 2017) - Ikudome, Sachi; Mori, Shiro; Unenaka, Satoshi; Kawanishi, Masashi; Kitamura, Takahiro; Nakamoto, Hiroki
The study examined the effect of a body-mass-based home exercise program on cognitive functioning among 170 male and female elderly people (52-81 years). This program comprised five kinds of resistance exercises that elderly people can perform at home without supervision or specialized equipment using only their body mass for resistance. Various cognitive tasks were used to assess cognitive functioning, including a simple reaction task, Go/No-Go reaction task, Stroop task, serial subtraction task, and coincident timing task. These tasks were performed before and after a 3-month body-mass-based home exercise program. Although there were no significant improvements in the simple reaction and coincident timing tasks, significant improvement was shown in the Go/No-Go reaction task and serial subtraction task. This study shows that even simple resistance exercise, using only body mass for resistance, may be an effective method for preventing age-related cognitive decline of inhibitory control and working memory among elderly people.